2015
DOI: 10.1021/jp508100s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionic Size on Solvate Stability of Glyme-Based Solvate Ionic Liquids

Abstract: A series of binary mixtures composed of glymes (triglyme, G3; tetraglyme, G4; pentaglyme, G5) and alkali-metal bis(trifluoromethanesulfonyl)amide salts (M[TFSA]; M = Li, Na, and K) were prepared, and the correlation between the composition and solvate stability was systematically investigated. Their phase diagrams and Raman spectra suggested complexation of the glymes with M[TFSA] in 1:1 and/or 2:1 molar ratio(s). From isothermal stability measurements, it was found that the formation of structurally stable co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(176 citation statements)
references
References 67 publications
10
164
1
1
Order By: Relevance
“…Many types of liquid organic solvents, including linear ethers such as glymes (monoglyme, diglyme, triglyme, and tetraglyme), [ 57,162,163 ] cyclic ethers (1,2-dioxolane and THF), [ 26,85 ] sulfone, [ 43,164 ] carbonates, [ 17,38,165,166 ] and ionic liquid, [ 75,167 ] have been investigated for their effect on the performance of sulfur cathodes. On the basis of knowledge about sulfur redox chemistry, early efforts focused on solvents with high solubility to polysulfi des for better utilization of the active material.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 99%
“…Many types of liquid organic solvents, including linear ethers such as glymes (monoglyme, diglyme, triglyme, and tetraglyme), [ 57,162,163 ] cyclic ethers (1,2-dioxolane and THF), [ 26,85 ] sulfone, [ 43,164 ] carbonates, [ 17,38,165,166 ] and ionic liquid, [ 75,167 ] have been investigated for their effect on the performance of sulfur cathodes. On the basis of knowledge about sulfur redox chemistry, early efforts focused on solvents with high solubility to polysulfi des for better utilization of the active material.…”
Section: Solvents' Impact On the Dissolved Polysulfi De Speciesmentioning
confidence: 99%
“…8,9,19 Systematic studies on the glyme-Li salt mixtures identified their characteristic features. 22,23 These studies, and a subdivision of solvate ILs based on their structural stability, are summarized in our recent perspective article. 8,9,12,13,20 The ionic nature of the equimolar mixtures is dominated by the Lewis basicity of the paired anion species.…”
Section: Introductionmentioning
confidence: 99%
“…Brouillette's and Henderson's groups previously performed pioneering work on the phase diagrams and solvate a Department of Chemistry and Biotechnology, Yokohama National University, structures of a series of glyme-Li salt mixtures. 23 Glyme-Li and glyme-Na systems with equimolar mixtures of ClO 4 À or other imide anions can also be referred to as solvate ILs. 31,32 Bruce et al reported the selective ion transport behavior in glyme-LiAsF 6 complex-based solid electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36][37] Given that a large number of combinations of metal salts and ligands are available to form a complex, we can play with different types of complexes, some of which have the potential to form solvate ILs. 38 Moreover, one may introduce a new functionality into the solvate ILs to form, for example, stimuli-responsible ILs by designing the components of the complexes. Of course, the application of the solvate ILs is not limited to electrochemical devices, but they have already been tested as reaction media for organic synthesis 39 and as the media for CO 2 capture.…”
Section: Discussionmentioning
confidence: 99%